Manajemen daya tarik wisata religi studi kasus makam Habib Ahmad Bin Ali Bafaqih, Yogyakarta - Tuti Panghastuti; Aisyah Shalawati (STIE Pariwisata API Yogyakarta, 2022)
This study aims to find out how the management of religious tourism attractions in the Tomb of Habib Ahmad bin Ali Bafaqih and find out what are the supporting and inhibiting factors for the management of religious tourism attractions. The type of this research is descriptive qualitative research with data collection methods used are interviews, observation and documentation. The results showed that the management of religious tourism at the tomb of Habib Ahmad Bafaqih was managed directly by the heirs by implementing management functions, namely by planning, organizing, mobilizing and supervising the program of religious activities in the tomb.